2017
DOI: 10.1097/mpg.0000000000001643
|View full text |Cite
|
Sign up to set email alerts
|

Induction Therapy With Biosimilar Infliximab in Children With Crohn Disease

Abstract: Induction therapy with CT-P13 in children with CD is effective. The profile appears similar to that reported for the reference infliximab. No unexpected adverse events occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
4
32
1
Order By: Relevance
“…They reported one acute infusion reaction, but no unexpected adverse events. 13 A prospective study on paediatric patients introduced to CT-P13 showed a decline in median calprotectin levels from 840 to 250 μg/g in 17 patients at week 12 (P = .008) (14). Our study observed therapeutic responses in 90% of the patients during F I G U R E 1 Proportion of anti-tumour necrosis factor α-naïve paediatric patients with IBD on maintenance therapy with infliximab or its biosimilar.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…They reported one acute infusion reaction, but no unexpected adverse events. 13 A prospective study on paediatric patients introduced to CT-P13 showed a decline in median calprotectin levels from 840 to 250 μg/g in 17 patients at week 12 (P = .008) (14). Our study observed therapeutic responses in 90% of the patients during F I G U R E 1 Proportion of anti-tumour necrosis factor α-naïve paediatric patients with IBD on maintenance therapy with infliximab or its biosimilar.…”
Section: Discussionmentioning
confidence: 58%
“…The following year, the same authors reported outcomes to induction therapy with CT-P13 in 36 patients with paediatric IBD, with assessments performed before the infusion and at week 14. 13 When they used the Paediatric Crohn's Disease Activity Index, they observed a clinical response in 86% and clinical remission in 67% of the patients. Faecal calprotectin levels or trough level measurements were not available.…”
Section: Discussionmentioning
confidence: 99%
“…In the Norwegian study by Jahnsen et al, infusion reaction occurred in 1 CD and 1 UC patients, rate of adverse event was 2.2% and 3.1% in CD and UC [40]. The studies from Poland revealed that safety profile is similar to that reported for the reference IFX and adverse event rate did not differ significantly either in CD or in UC before and after the switch from IFX to CT-P13 [38,44]. The Hungarian multicenter study revealed adverse events in 17.1% of all patients.…”
Section: Safety and Tolerabilitymentioning
confidence: 77%
“…A study of 96 patients comparing the efficacy of infliximab compared to biosimilar CT-P13 in maintaining remission in inflammatory bowel diseases found similar long-term outcomes and safety between the two treatment groups[ 10 ]. Additionally, a study on CT-P13 in pediatric Crohn’s disease reported remission after three doses in 24 of 36 patients and clinical response in 31 of 36[ 11 ]. CT-P13 is currently marketed as Remsima™ and Inflectra™.…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%